Antioxidant effectiveness of ground roasted coffee in raw ground top round beef with added sodium chloride. Issue 1 (January 2015) - Lin, Crystal; Toto, Criselda; Were, Lilian
Abstract Rosemary extracts are commonly utilized in the meat industry to control oxidation. Roasted coffee, a source of antioxidants, was investigated for its utility as a less costly rosemary replacement for meat. Ground beef with 0–2 g salt/100 g was treated with rosemary extract (0.1 mL/100 g, positive control), light roasted, medium roasted or dark roasted coffee (0.1 g/100 g) and stored for 7 days at 4 °C. Coffee was characterized by melanoidins, chlorogenic acid content, and metal chelation. Ground beef was evaluated for CIE L* (lightness), a* (redness), and b* (yellowness) values and lipid oxidation products. Increasing roast degree increased melanoidins and decreased chlorogenic acids. Salt treated samples developed higher thiobarbituric reactive substances values. Dark roasted coffee showed the greatest antioxidant capacity in salted beef after 7 days. Rosemary maintained the highest a* for all salt levels. Of all antioxidants, dark roast coffee showed the greatest % aldehyde inhibition for pentanal (86%), hexanal (90.3%), octanal (74.8%), and nonanal (60.3%) after 7 days in 2 g/100 g salted beef compared to control without added antioxidants. These results suggest that roasted coffee could act as an effective natural antioxidant in beef, extending its shelf-life, even in the presence of NaCl, which typically increases lipid oxidation levels.